ASSEMBLEIA DE DEUS MINISTÉRIO BELÉM EM ITAPECERICA DA SERRA: TRANSFORMAÇÕES SOCIOCULTURAIS DOS USOS E COSTUMES - OLIVEIRA, ANDRÉ APARECIDO DE (2016)
This thesis aims to analyze the sociocultural changes relating to the uses and customs of God Ministry Bethlehem Assembly church in Itapecerica da Serra in Crispim neighborhood. From this perspective we try to understand the reasons that underlie today the ideological discourse and conservative church study on the flexibility and new paradigms concerning the uses and customs. Currently the Assembly of God church in Itapecerica da Serra goes through a process of change and reinterpretation on their uses and customs. We intend to discuss the possibility that such changes are derived from contact with different existing Pentecostalism in Itapecerica da Serra, and also of their own socio-cultural development of society. As a methodological process used historical items, data published through books, articles, newspapers, the church itself that assist in comparison of the data found in interviews with Assemblies of Itapecerica da Serra. The results of this research are presented in three chapters whose central axis is the discussion of sociocultural transformations of the uses and customs. Keyword: Assembly